Cerebellar Involvement in an Immunocompetent Patient Presenting with Progressive Multifocal Leukoencephalopathy - Garcia-Carretero, Rafael (Case Rep Neurol Med, 2017)
Progressive multifocal leukoencephalopathy (PML) is a demyelinating disease caused by the JC virus, a polyomavirus that can be reactivated under certain immunosuppressive conditions, such as AIDS, immunomodulatory therapy, and haematological malignancies. However, a few cases of immunocompetent patients have been reported in which no immunodeficiency was present. We describe the case of an 83-year-old immunocompetent man who presented with severe cerebellar symptoms with an MRI scan suggestive of severe demyelinating disease. We were not able to identify any occult immunosuppression or malignancy in our patient.